Contracts for difference support the expansion of renewable energy sources while reducing electricity price risks - Mats Kröger; Karsten Neuhoff; Jörn C. Richstein (DIW Weekly Report, 2022)
The German Federal Government passed the "Easter Package" in July 2022, which envisages a number of measures for the expansion of renewable energy sources. The package retains sliding market premiums as a remuneration mechanism, which protect electricity producers unilaterally, while contracts for difference (CfDs), which also protect electricity customers, are only used in the offshore wind sector. However, CfDs could lead to a reduction in financing costs and reduce electricity price risks for producers as well as households and companies. The decline in financing costs would strengthen the expansion of renewable energy sources. In this context, a simplified market value model and further developing the reference yield model could ensure a system-friendly expansion of renewable energy sources.
Keywords: Q40; Q41; Q42; Q48; D44; G32; 330; Contracts for Differences; Renewable Energy; Support Mechanisms